2020
DOI: 10.1111/aji.13290
|View full text |Cite
|
Sign up to set email alerts
|

Intralipid treatment for women with reproductive failures

Abstract: Does intravenous intralipid treatment for reproductive failure enhance live births? The answer to this question is yes, BUT only in patients that have a diagnosis of recurrent implantation failure (RIF) or recurrent pregnancy loss (RPL) loss AND demonstrate elevated NK (natural killer) cell density in their endometrial biopsy. Live birth rates have been reported between 33% and 42% among women displaying elevated NK activity with a diagnosis of RIF and 75% and 91% among women experiencing RPL after intralipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…On the same note of immune modulating therapies, several studies have suggested the potential effect of intralipids in modulating the cytotoxicity of NK cells along with the secretion of pro-inflammatory cytokines [87][88][89]. Intralipid therapy is a 20% intravenous fat emulsion, which has been introduced in the medical practice for parenteral nutrition [90].…”
Section: Intralipid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…On the same note of immune modulating therapies, several studies have suggested the potential effect of intralipids in modulating the cytotoxicity of NK cells along with the secretion of pro-inflammatory cytokines [87][88][89]. Intralipid therapy is a 20% intravenous fat emulsion, which has been introduced in the medical practice for parenteral nutrition [90].…”
Section: Intralipid Therapymentioning
confidence: 99%
“…Intralipid molecules act as ligands for the G-protein-coupled receptor that results in activating the cAMP signaling pathway that is associated with the NFkB pathway. The NFkB pathway ultimately modulates the transcription of the DNA and controls essential immune responses [89]. Several studies have suggested that intralipid therapy may be employed in cases of reproductive failure.…”
Section: Intralipid Therapymentioning
confidence: 99%
“…Immunotherapy has also been a focus of research in these cohorts. Recent systematic reviews have sought to establish if any immunotherapies have made a significant impact on live birth rates, pregnancy rates or miscarriage rates in RM cohorts [125][126][127][128] and RIF cohorts 129,130 , as have a number of literature reviews [131][132][133][134][135] . While Achilli et al looked at women undergoing IVF with and without RM, no specific work has been done in infertility cohorts experiencing RM.…”
Section: Male Fertilitymentioning
confidence: 99%
“…6,7 Other recent studies discuss the effectiveness in RPL treatment of some immunomodulatory agents such as paternal leucocyte immunization (PLI), intravenous immunoglobulin (IVIg), filgrastim and intralipid. [8][9][10][11] Among these, the lipid emulsion therapy (LET) has emerged as a possible new intervention therapy for women stricken by RPL and RIF. The cellular mechanisms by which intralipid acts are not completely understood, but some authors believe that the lipid emulsion restores the NK cells' abnormal activity to normal levels thereby improving embryo implantation.…”
mentioning
confidence: 99%